Analysis of histopathological examination of the hysterectomy specimens in a north Indian teaching institute - Verma, Deepti; Singh, Pankaj; Kulshrestha, Rupita (International Journal of Research in Medical Sciences, 2016)
Background: This was a retrospective study in which the histopathological examination (HPE) of the specimens of all the hysterectomies done for the non-oncological causes in the Mayo Institute of Medical Sciences (MIMS), Barabanki, India from January 2015 to July 2016 were analyzed. The aim of the study was to assess the range of pathological lesions in the hysterectomy specimens and correlation of the preoperative diagnosis with the histopathological diagnosis. Methods: This was a retrospective study which included all the patients who underwent hysterectomy for the non – oncological gynecological causes in Mayo Institute of Medical Sciences, Barabanki, Uttar Pradesh, India over a span of 19 months, from January 2015 to July 2016. Results: A total of 152 hysterectomies were done for the non-oncological causes in the department of obstetrics and gynecology, MIMS, during the study period. Among these, 95 (62.5%) were done by the abdominal route and 57 (37.5%) were done by vaginal route. Mean age of the patients were 50.86±6.9 years, the mean age for vaginal hysterectomy being higher as compared to the abdominal hysterectomy. Uterovaginal prolapse (37.5%) was the most common preoperative indication, while the fibroid uterus (25.65%) was the commonest indication for the abdominal hysterectomy. Other common indications were dysfunctional uterine bleeding (DUB, 9.87%) and ovarian mass (7.89%). Fibroid uterus in the myometrium, chronic cervicitis in the cervix and functional cysts in the ovaries were the commonest histopathology noted. Adenomyosis was the most missed pathology preoperatively. Patients operated with a preoperative diagnosis of DUB had least HPE correlation. Unremarkable HPE was found in 12.5% cases, all were operated for uterovaginal prolapse Conclusions: Justification of hysterectomy is proved when the HPE report is compatible with the preoperative diagnosis; hence HPE of all hysterectomy specimens should be done and analyzed.